Hypoglycemic Effect of Camel Milk on Monosodium Glutamate Diabetes Induced-Rabbits - A. Z., Sanusi; Ahmad, Yahaya Mohammed; Yahaya, Jamilu Runka; Asambe, Aondoakaa; Joshua, Felicia (International Journal For Research In Agricultural And Food Science, 2020)
The hypoglycemic efficacy of camel milk on monosodium glutamate diabetes induced-rabbits was evaluated in this study. 20 Adult male rabbits weighing between 1.2 - 1.7 kg were randomly distributed into four groups of five rabbits each. Diabetes was induced using monosodium glutamate (MSG) at a dose of 6.66mg/ml of drinking water given ad libitum for two weeks to rabbits in three groups (T2, T3 and T4). T1 served as control and received no MSG. Diabetic state was confirmed using a glucometer (Accu-check® and Accu-check test strips). Two diabetic groups of rabbits received raw camel milk T2 and T3 while one diabetic group (T4) of rabbits received Glucophage®. T2 received 2.5mls of raw camel milk daily for 2 weeks while T3 received 5mls of raw camel milk daily for the same duration. Rabbits in T4 were treated with 18.75 mg/kg of Glucophage daily. It was noted that MSG led to increase in body weight of the diabetic rabbits. Rabbits in T4 showed most significant decline in blood glucose levels followed by T3. T2 recorded the least decline in blood glucose. It was concluded that camel milk had a significant hypoglycemic effect at 5ml/day on diabetic rabbits and it was recommended that further studies be carried out to determine if camel milk has hypoglycemic effect on diabetic patients and the optimal amount of camel milk that averts hyperglycemia as well as to establish the mechanism of action of this hypoglycemic effect.